PERBANDINGAN BIAYA DAN WAKTU SISTEM DILATASI BALOK KANTILEVER DAN DUA KOLOM PADA PROYEK GEDUNG BERTINGKAT KAMPUS B UNIVERSITAS AIRLANGGA - Monika Natalia; Riswandi Riswandi; Yan Partawijaya; Jajang Atmaja; M. Iqbal Kuswandi (LPPM Universitas Abdurrab, 2022)
Almost all regions of Indonesia are geographically vulnerable to natural disasters, earthquake. One way to implement a very long and structurally stable building design in the event of an earthquake or other circumstances is to provide a dilation system for the building. This research was conducted in a multi-storey parking building project at Airlangga University Campus B which applies a cantilever beam dilatation system and will be compared with a two-column dilatation system in terms of cost and time. Cantilever beam dilatation is a structural separation that uses a beam structure with one end having a clamp and the other end is free, while two-column dilatation is a structural separation that uses two columns side by side with a certain distance. From the results of the study, it was found that the cost of structural work with cantilever beam dilatation was Rp. 76,755,100,000, - and for two-column dilatation is Rp. 76.063.550.000,- while the total project time with cantilever beam dilatation is 451 working days, and for two-column dilatation is 447 working days. The application of two-column dilatation is 0.9% more cheaper and four days earlier than the application of the cantilever beam dilatation system.